The history of Kanagawa (Yokahama, Japan, 1985)
This presents the history of one region of Japan in beautiful photos, historic art, and text in English. Kanagawa Prefecture is located within Japan's premiew region and is part ofthe nation's Pacific Belt. It is the third largest after Tokyo and Osaka. Blessed with natural beauty and rich history including the Hakone and Kamakura areas, this book is important in understanding modern
Keywords: Kanagawa-ken (Japan); History